Why Not Blow the Whistle on Health Care Insurance Fraud? Evidence from Jiangsu Province, China - Wang D; Zhan C (Dove Medical Press, 2022)
Dandan Wang, Changchun Zhan School of Management, Jiangsu University, Zhenjiang, People's Republic of ChinaCorrespondence: Changchun Zhan, Tel +86-15952808385, Email Zcc1973@126.comPurpose: To identify the factors that influence whistleblowing behavior as it relates to health care insurance fraud in Jiangsu Province, China.Methods: To construct a factor model and formulate research hypotheses using the Motivation-Opportunity-Ability framework. We designed a questionnaire containing 24 items and distributed it on-site to 2081 respondents in Jiangsu Province, China. Afterward, we applied structural equation modeling to validate the research hypotheses.Results: Policy awareness negatively contributes to whistleblowing behavior, risk perception does not reduce the incentive to blow the whistle, and an inability to recognize fraud is another critical barrier to converting whistleblowing intentions into behavior.Conclusion: Practices that are likely to promote citizen whistleblowing on insurance fraud may focus on the constraints identified by the comprehensive Motivation-Opportunity-Ability framework.Keywords: health care insurance fraud, whistleblowing behavior, Motivation-Opportunity-Ability framework, structural equation modeling